Input Technologies and Techniques (2007) - Hinckley, Ken (The Human-Computer Interaction Handbook: Fundamentals, Evolving Technologies and Emerging Applications, Second Edition, 2007)
Exploring the evolution in how people use and work with technology, the second edition of The Human-Computer Interaction Handbook captures the most important scientific and technical know-how in the field of HCI. It provides an updated, comprehensive overview of important research in the field, including insights directly applicable throughout the process of developing effective interactive information technologies. It features cutting-edge advances to the scientific knowledge base and visionary perspectives and developments that will fundamentally transform the way in which researchers and practitioners view the discipline. As the seminal volume of HCI research and practice, the second editionfeatures contributions from a selection of eminent professionals in the field worldwide. It stands alone as the most essential resource available on the market. This edition of the volume thoroughly covers issues of accessibility and diversity, such as aging, literacy, hearing, vision, physical disabilities, and children. Additional topics addressed are sensor based interactions; tangible interfaces; augmented cognition; cognition under stress; ubiquitous and wearable computing; privacy and security. With contributions from over 130 researchers and professionals, over 5,500 references, 400 figures, and 100 tables, the book provides a wealth of data and a fresh perspective on the field. New topics and authors ensure the revision contains new information and insights, the latest in research and practice, while retaining its reputation for presenting authoritative information in an accessible manner.